Identification of an unrecognized circRNA associated with development of renal fibrosis - Zhu, Yun; Yan, Weimin; Xu, Shuangyan; Yu, Xiaochao; Sun, Shuo; Zhang, Shaoxiong; Zhao, Ran; Tao, Jiayue; Li, Yunwei; Li, Cuie (Frontiers in Genetics, 2023)
Introduction: Circular RNA (circRNA) plays an essential role in the development of renal fibrosis (RF), but its regulative mechanism remains elusive. Methods: In the current study, the RF model of the rat was established, and RNA-sequencing and real-time polymerase chain reaction (qRT-PCR) experiments were implemented. Subsequently, cell apoptosis and proliferation were carried out. Finally, the iTRAQ proteomics analyses were carried out for the samples. Results: It indicated that circRNA_0002158, a newly discovered circRNA, is highly expressed in kidneys with fibrosis, implying that it might be associated with the development of RF. Subsequently, the overexpression (OE) and knockdown of circRNA_0002158 were been carried out in the human kidney epithelial cell line (HK-2) cells, and the results indicated that the circRNA_0002158 could inhibit apoptosis, and accelerate proliferation. Furthermore, the kidney injury-related factors including Fibronectin (FN) and plasminogen activator inhibitor-1 (PAI-1) were decreased in OE of circRNA_0002158 HK-2 cells, while the results were reversed in knockdown of circRNA_0002158 HK-2 cells. Finally, the iTRAQ proteomics analyses were carried out for the samples from OE and its control, and the GO and KEGG analyses showed that multiple functional pathways were associated with the development of RF. Conclusions: CircRNA_0002158 might be a potential treatment target for ameliorating the progression of RF.